2017
DOI: 10.1128/mspheredirect.00340-17
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Validation of Leishmania donovani Lysyl-tRNA Synthetase Shows that It Is Indispensable for Parasite Growth and Infectivity

Abstract: Aminoacyl-tRNA synthetases are housekeeping enzymes essential for protein translation, providing charged tRNAs for the proper construction of peptide chains. These enzymes provide raw materials for protein translation and also ensure fidelity of translation. L. donovani is a protozoan parasite that causes visceral leishmaniasis. It is a continuously proliferating parasite that depends heavily on efficient protein translation. Lysyl-tRNA synthetase is one of the aaRSs which charges lysine to its cognate tRNA. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The KMSKS motif is replaced by KKIKT, and unlike Pyrococcus horikoshii ArgRS [27], the first lysine residue of this motif, Lys491, interacted with the adenine of ATP, suggesting its role in ATP-PPi exchange reaction. We also synthesized ATP resembling inhibitors knowing that analogs of ATP such as cladosporin are potent inhibitors of aaRSs [54,55]. Of them, the ones that possessed halogen groups attached to the para position or methyl groups linked to the ortho and meta positions of the third benzene ring augmented their potency.…”
Section: Discussionmentioning
confidence: 99%
“…The KMSKS motif is replaced by KKIKT, and unlike Pyrococcus horikoshii ArgRS [27], the first lysine residue of this motif, Lys491, interacted with the adenine of ATP, suggesting its role in ATP-PPi exchange reaction. We also synthesized ATP resembling inhibitors knowing that analogs of ATP such as cladosporin are potent inhibitors of aaRSs [54,55]. Of them, the ones that possessed halogen groups attached to the para position or methyl groups linked to the ortho and meta positions of the third benzene ring augmented their potency.…”
Section: Discussionmentioning
confidence: 99%
“…This study also reported the 3D structure of C. parvum LysRS in complex with cladosporin and L-Lys. LysRS-1 (KRS-1) from L. donovani is an essential gene ( 53 ).…”
Section: Inhibitors Against Parasite Aminoacyl-trna Synthetasesmentioning
confidence: 99%
“…Furthermore, cladosporin could retard parasite growth proving that the LysRS gene is indeed essential for its survival. 50 …”
Section: Research Accomplished On Trypanosomatid Aminoacyl Trna Synth...mentioning
confidence: 99%
“…Thus, it can be exploited for the development of antitrypanosomal drugs, keeping in mind the differences present in the two residues present in the ATP binding pocket. Furthermore, cladosporin could retard parasite growth proving that the LysRS gene is indeed essential for its survival …”
Section: Research Accomplished On Trypanosomatid Aminoacyl Trna Synth...mentioning
confidence: 99%